RESEARCH OF REPRESENTATIONS OF STUDENTS ABOUT MODERN UKRAINIAN HUMAN (GENDER ASPECTS) - Strebkova, Juliia (Київський національний університет імені Тараса Шевченка, 2017)
The article represents the results of a 5-year research using the method "Draw a modern Ukrainian human". The study involved students of the National Technical University of Ukraine "Igor Sikorsky Polytechnic Institute": Institute of Mechanical Engineering, Faculty of Sociology and Law, Faculty of Chemical Engineering and Printing and Publishing (different years of study). Both STEM and social and humanitarian subjects were represented: "Engineering Mechanics", "Mechanical Engineering", "ChemicalTechnology", "Packaging production technology", "Publishing and Editing", "Sociology", "Administrative Management" and other. In total, more than five hundred student works were analyzed. This article focuses on the gender aspects of this study. For the first time in Ukrainian studies projective drawing techniques were used to study the gender aspects of a Ukrainian person. The value and described diagnostic picture for the socialphilosophical studies of gender interaction is proved. The experimental formulations of the gender dilemma are described. It has been found out that the application of the described method removes bipolarity and opposition of male and female qualities. The paper contains examples of drawings and processed quantitative data in the form of diagrams. The results of gender research, of social meanings vs social structure of Ukrainian society, are generalized. It is proved that the concept of a Ukrainian person is gender-deformed. The obtained data confirm the results of previous studies in terms of the spread of stereotypical representations. For example, there are illustrations of beautification, works for the sake of beauty, oniomania, experiences of the inadequacy of one's own physicality with cultural standards and aesthetic ideals. There were no correlation between the number of girls surveyed and the number of human images of a woman. Revealed that the characters of our time, such as appliances and brands, found both male and female images. Among the painted Ukrainian symbols the most common are the trident, flag and embroidered shirt, which are both in male and female images. Wreaths are often combined with modern women's clothing. This confirms Ukrainian authors’ studies results, that the symbolism of Ukrainian clothing is a vivid illustration of the development and transformation of worldview imaginations of the Ukrainian people. Specified is need of revising the old school tests and pedagogical and psychological methods that form a child's distorted perception of a person. Keywords: gender studies, gender dilemma, projective methods, diagnostic picture, symbols.

Обґрунтована необхідність міждисциплінарного трансферу експериментальних даних у гендерних дослідженнях. Розглянуто можливість емпіричного соціально-філософського дослідження. Доведена цінність діагностичного малюнка для соціально-філософських досліджень ґендерної взаємодії. Описана експериментальна постановка ґендерної дилеми. З’ясовано, що застосування описаної методики знімає біполярність і протиставлення чоловічих та жіночих якостей. Вперше були застосовані проективні малюнкові техніки для дослідження ґендерних аспектів української людини. Робота містить приклади малюнків та опрацьовані кількісні дані у вигляді діаграм. Узагальнено результати ґендерного дослідження соціальних смислів та соціальної структури українського соціуму. Доведено, що уявлення про українську людину є ґендерно деформованими. Стверджується, що такі викривлені уявлення про жінок у суспільстві значно ускладнюють розробку державної політики і негативно позначаються на вирішенні суспільно-важливих завдань. Виявлено небезпеку, що і в майбутньому інтелектуальна, політична та економічна еліта не буде спроможною відповісти на виклики суспільства, бо орієнтується на уявлення, що не відповідають дійсності. Зазначено необхідність перегляду застарілих шкільних тестів, педагогічних і психологічних методик, що формують у дитинстві викривлене уявлення про людину. Ключові слова: ґендерні дослідження, ґендерна дилема, проективні методики, діагностичний малюнок, символи.
ДОСЛІДЖЕННЯ УЯВЛЕНЬ СТУДЕНТСТВА ПРО СУЧАСНУ УКРАЇНСЬКУ ЛЮДИНУ (ҐЕНДЕРНІ АСПЕКТИ)